2016
DOI: 10.1557/jmr.2016.62
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure and mechanical properties of ice-templated tungsten foams

Abstract: Tungsten foams with directional, controlled porosity were created by directional freeze-casting of aqueous WO 3 powder slurries, subsequent freeze-drying by ice sublimation, followed by reduction and sintering under flowing hydrogen gas to form metallic tungsten. Addition of 0.51 wt% NiO to the WO 3 slurry improved the densification of tungsten cell walls significantly at sintering temperatures above 1250°C, yielding densely sintered W-0.5 wt% Ni walls with a small fraction of closed porosity (,5%). Slurries w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…A route to significantly increase the range of metallic elements would be the use of metal oxide nanoparticles combined with subsequent annealing in a reducing atmosphere. Dunand and co‐workers developed a method of macroscopic 3D printing with oxide particles and showed that most oxides can be reduced to their metallic state after printing . Yet, the significant volume loss upon reduction of the oxide is a considerable drawback of this approach.…”
Section: Discussionmentioning
confidence: 99%
“…A route to significantly increase the range of metallic elements would be the use of metal oxide nanoparticles combined with subsequent annealing in a reducing atmosphere. Dunand and co‐workers developed a method of macroscopic 3D printing with oxide particles and showed that most oxides can be reduced to their metallic state after printing . Yet, the significant volume loss upon reduction of the oxide is a considerable drawback of this approach.…”
Section: Discussionmentioning
confidence: 99%
“…The intertwined dendritic structure of the ice-templated BM -alumina composite offers no direct path for cracks to propagate perpendicular to the loading axis, which serves to suppress brittle fracture in the BM. Although the present ice -templated BMalumina composites showed lack of plasticity in compression, the ductility of icetemplated BM composites may be enhanced by the infiltration of freeze -cast metals such as Mo [32] or W [18], which have been considered as a ductile reinforcement for BMs [2,13]. However, the best means to optimize the microstructure to improve both strength and ductility in these composites is still unclear, and consequently merits further investigation.…”
mentioning
confidence: 86%
“…From the perspective of processing BM -ceramic composites, freeze-casting (icetemplating) represents an effective technique to synthesize anisotropic foam materials using ice to generate bioinspired "nacre-like" hierarchical architectures [16][17][18]. Porosity can be modified between 0-100 % and lamellae thickness and spacing is tailorable at the micron-scale in the freeze-cast foams by controlling processing parameters [16][17][18][19].…”
mentioning
confidence: 99%
“…The process is schematically summarized in Figure 1. The effects of processing parameterspowder fraction in the slurry, freeze-casting and sintering temperatures as well as the influence of nickel -on the final scaffold microstructure, in particular open porosity and structural wavelength, have been reported in detail in a previous publication 25 gravitational forces. After solidification and cooling of the composites to room temperature, cylindrical compressive specimens (5-6 mm diameter and height/diameter aspect ratio of 2:1) were machined on a lathe.…”
Section: Composite Synthesismentioning
confidence: 99%